The Effectiveness Of Oxytocin Massage On Breast Milk Letdown In Postpartum Mothers In The Delivery Room Of Ampelgading Community Health Center - Qurota Akyuni; Nila Widya Keswara (CV. AFDIFAL MAJU BERKAH, 2026)
Babies get all the nutrients they need to grow and develop optimally from breast milk, making it the ideal food source. Breast milk secretion issues are frequent among new moms, especially in the first few days after giving birth. One non-pharmacological approach to increasing milk production and secretion is oxytocin massage, which works by stimulating the release of the hormone oxytocin. In 2025, the goal of 80% was not met at Ampelgading Public Health Center, Ampelgading District, where the coverage of exclusive breastfeeding remained at 72%. The purpose of this research was to find out whether postpartum women could increase their milk production by massaging their breasts with oxytocin. The researchers in this study used a one-group pretest-posttest design based on previous research. Thirty pregnant women who had just given birth were randomly selected using the complete sampling technique. For three days, we monitored the secretion of breast milk both before and after performing an oxytocin massage. The Wilcoxon-marked assessment test was used to evaluate the data, with a significance level of α = 0.05 being used. According to the data, the majority of participants were between 26 and 30 years old, had experienced a termination of employment, had a minimum of Junior High School Education, were unemployed, and were among the youngest participants (10 respondents; 33.3%). After receiving oxytocin massage, the average amount of breast milk released increased from 6.93 cc to 24.83 cc. Statistically significant changes in breast milk secretion were seen before and after oxytocin massage administration, as indicated by a p value of 0.000 (p < 0.05) on the Wilcoxon Signed Rank test. Postpartum women who get an oxytocin massage report an increase in their milk production. Midwives may advise oxytocin massage as a postpartum intervention to help the mother secrete more breast milk.